Effectiveness of a Yoga-Based Intervention in Alleviating Depressive Symptoms Among Older Adults: A Case Study - A, Arina Desi; Uliyah, Musrifatul; Susanty, Ade (Jurnal Keperawatan Muhammadiyah, 2025)
Depression is a prevalent mental health condition among older adults and significantly impairs their overall quality of life. This study examines the effectiveness of a yoga-based intervention in reducing depressive symptoms in two elderly individuals with moderate depression residing at Griya Werdha Nursing Home in Surabaya, Indonesia. A case study approach was employed, implementing a four-day yoga program with daily sessions lasting 30–40 minutes. Depression levels were assessed using the Geriatric Depression Scale (GDS) before and after the intervention. Both participants demonstrated a marked decrease in GDS scores, transitioning from moderate depression to a non-depressed state. The observed improvement is attributed to enhanced physical and psychological functioning, along with potential reductions in cortisol levels. These findings suggest that yoga may represent a safe and effective non-pharmacological approach for managing depression in older populations.